The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijerph20043051
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Recycling and Utilization of Phosphate from Wastewater Using LDHs-Modified Biochar

Abstract: The excessive application of phosphate fertilizers easily causes water eutrophication. Phosphorus recovery by adsorption is regarded as an effective and simple intervention to control water bodies’ eutrophication. In this work, a series of new adsorbents, layered double hydroxides (LDHs)-modified biochar (BC) with different molar ratios of Mg2+ and Fe3+, were synthesized based on waste jute stalk and used for recycling phosphate from wastewater. The prepared LDHs-BC4 (the molar ratio of Mg/Fe is 4:1) has signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Figure 1 shows the nitrogen adsorption-desorption isotherms and pore size distribution of MFBCs and MBC. According to the Brunauer-Emmet-Teller theory, MFBCs exhibit type IV isotherms in the relative pressure range of 0.1-0.9, indicating that MFBCs are mesoporous [13]. The results showed that the adsorption capacity of MFBCs and MBC gradually increased with the increase in relative pressure, and the adsorption/desorption curve of the MBC in the low-pressure region (0.15-0.40 relative pressure (P/P 0 )) showed a significant increase, indicating that MBC contains more abundant mesoporous and microporous structures than MFBCs [14].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the nitrogen adsorption-desorption isotherms and pore size distribution of MFBCs and MBC. According to the Brunauer-Emmet-Teller theory, MFBCs exhibit type IV isotherms in the relative pressure range of 0.1-0.9, indicating that MFBCs are mesoporous [13]. The results showed that the adsorption capacity of MFBCs and MBC gradually increased with the increase in relative pressure, and the adsorption/desorption curve of the MBC in the low-pressure region (0.15-0.40 relative pressure (P/P 0 )) showed a significant increase, indicating that MBC contains more abundant mesoporous and microporous structures than MFBCs [14].…”
Section: Resultsmentioning
confidence: 99%